Blaschke Products and Their Applications - Mashreghi, Javad; Fricain, Emmanuel (Fields Institute Communications,, 2013)
Blaschke products have been researched for nearly a century. They have shown to be important in several branches of mathematics through their  boundary behaviour, dynamics, membership in different function spaces,  and the asymptotic growth of various integral means of their derivatives.   This volume presents a collection of survey and research articles that examine Blaschke products and several of their applications to fields  such as approximation theory, differential equations, dynamical  systems, and harmonic analysis. Additionally, it illustrates the  historical roots of Blaschke products and highlights key research on this topic.   The contributions, written by experts from various fields of  mathematical research, include several open problems. They will  engage graduate students and researchers alike, bringing them to the forefront of research in the subject.